Analisis Faktor-Faktor yang Mempengaruhi Minat Menggunakan Paylater dengan Religiusitas Sebagai Variabel Moderasi - Nur Habibah Nasution; Misbahul Munir (Al-Buhuts, 2023)
The purpose of the research was to analyze the influence of financial literacy, perceived risk and perceived ease of use on the interest in using paylater services with religiosity as a moderating variable among college students in Malang City. This study used a quantitative approach with the study population being students of the Faculty of Economics and Business or the and Faculty of Economics at UIN Malang, Brawijaya University, and State University of Malang. The sampling technique used the Slovin formula and get 390 samples. Data  collection technique by distributing questionnaires and then the collected data was processed using SPSS 25 software. The results of this research indicate that financial literacy and ease of use have a significant positive relationship with intention to use paylaters, while risk perception has no effect on intentions to use paylaters. The  religiosity as moderator is able to weaken the relationship between perceived ease of use  to intention to use  paylater.  Financial literacy and perceived of risk of interest in using paylater cant be moderate by religiosity variable